1990
DOI: 10.1007/bf01973372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the peroxisome proliferator perfluorodecanoic acid on growth and lipid metabolism in Sprague Dawley rats fed three dietary levels of selenium

Abstract: The possible interrelationships between the effects of dietary selenium and perfluorodecanoic acid (PFDA) on growth and lipid metabolism were studied in the male Sprague Dawley rat. Rats were divided into groups and placed on diets containing three levels of selenium (0.04, 0.2, and 1.0 ppm as sodium selenite). Two weeks later, half the rats in each group received a single 35 mg/kg IP injection of PFDA in corn oil, while their pair-fed companion received only vehicle. Rats injected with PFDA stopped gaining we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…In a previous study (Borges et al 1990), we reported that a single 35 mg/kg IP injection of PFDA increased the activity of fatty acyl-CoA oxidase, the first enzyme in peroxisoma113-oxidation. In contrast, total peroxisomal [3-oxidation was decreased.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In a previous study (Borges et al 1990), we reported that a single 35 mg/kg IP injection of PFDA increased the activity of fatty acyl-CoA oxidase, the first enzyme in peroxisoma113-oxidation. In contrast, total peroxisomal [3-oxidation was decreased.…”
Section: Introductionmentioning
confidence: 80%
“…The procedure yielded 99% pure PFDA (Reich et al 1987 (Borges et al 1990). The animals, housed in a controlled environment maintained at 22~ with a 12 h light (0600-1800) dark cycle, were randomly assigned to one of six groups (0.0, 0.3, 1.0, 3.0, 10.0, or 30.0 mg PFDA/kg) of five animals each and fed a modified AIN-76A purified diet (Bieri et al 1977(Bieri et al , 1980 as described previously (Borges et al 1990). Tap water and the purified diet, fed in screw cap jars fastened to the side of the cage, were provided ad libitum.…”
Section: Reagents and Chemicals Perfluorodecanoic Acid (Pfda) Obtaimentioning
confidence: 99%
“…Additionally, GSH and GSSG can be eliminated from liver by the action of transpeptidases and via bile secretion [13,31]. Contrast to many peroxisome proliferators, PFDA treatment lowers the flux through peroxisomal b-oxidation, even though it induced peroxisomal FAO activity as other peroxisome proliferators [32,33]. PFDA inhibits several enzymes involved in peroxisomal b-oxidation, which may decrease the rate of peroxisomal b-oxidation and H 2 0 2 production [34], but it had no effect on GSHPX [14].…”
Section: Figurementioning
confidence: 99%
“…Biomonitoring studies have shown that PFOS and PFOA are present in humans and wildlife around the world (Lehmler 2005). Although the toxicological effects of these chemicals are still under investigation, some animal studies have suggested that PFAAs affect the liver, neonatal development, the immune system, and hormone levels (Borges et al 1990(Borges et al , 1992Lau et al 2007;Andersen et al 2007;Roos et al 2008). Therefore, PFAAs have been found to possess many of the characteristics of persistent organic pollutants.…”
Section: Introductionmentioning
confidence: 99%